A critical assessment of the current pharmacotherapy for the treatment of embolic strokes of undetermined source. (24th May 2022) - Lattanzi, Simona; Acampa, Maurizio; Norata, Davide; Broggi, Serena; Caso, Valeria
ABSTRACT: Introduction: 'Embolic stroke of undetermined source' (ESUS) is a term coined to identify non-lacunar stroke whose mechanism is likely to be embolic, and the source remains unidentified. The best antithrombotic treatment for preventing stroke recurrence in this population has not been delineated. Areas covered: The authors summarize and critically appraise the currently available evidence about the antithrombotic treatment for preventing stroke recurrence in patients with ESUS. Randomized trials addressing this topic were identified through MEDLINE (accessed by PubMed, as of November 2021, week 4). Expert opinion: Recent randomized trials have failed to demonstrate a significant benefit of direct oral anticoagulants over aspirin in reducing the recurrence of cerebral infarctions in unselected cohorts of patients with ESUS. The heterogeneity and often overlap of embolic sources may be possible explanations for the overall absence of a benefit of oral anticoagulants in ESUS as a single homogeneous entity. The results of these trials and their subgroup analyses have provided important cues to understand the pathophysiology of ESUS. They have, furthermore, increased in the interest in researchers in identifying distinct etiological phenotypes within this stroke population. There is a good rationale for ongoing and future investigations in order to tailor antithrombotic treatment according to individual features of patients with ESUS.